Man the hunted : primates, predators, and human evolution - Hart, Donna. (Westview Press ; Perseus Books Group [distributor], 2009)
"Man the Hunted argues that primates, including the earliest members of the human family, have evolved as the prey of any number of predators, including wild cats and dogs, hyenas, snakes, crocodiles, and even birds. The authors' studies of predators on monkeys and apes are supplemented here with the observations of naturalists in the field and revealing interpretations of the fossil record. Eyewitness accounts of the "man the hunted" drama being played out even now give vivid evidence of its prehistoric significance. This provocative view of human evolution suggests that countless adaptations that have allowed our species to survive - from larger brains to speech - stem from a considerably more vulnerable position on the food chain than we might like to imagine. The myth of early humans as fearless hunters dominating the earth obscures our origins as just one of many species that had to be cautious, depend on other group members, communicate danger, and come to terms with being merely one cog in the complex cycle of life." "The expanded edition includes a new chapter that describes the ever-increasing evidence of predation on humans and claims that the earliest humans were neither hunters nor even the accomplished scavengers that many authorities have suggested. Furthermore, the authors provide evidence that as a prey species humans relied on cooperation as one of many predator avoidance mechanisms."--BOOK JACKET.